Effectiveness of Implementing Problem-Based Learning Modules to Improve Students' Science Literacy and Higher-Order Thinking - Sugiharti, Gulmah; Dalimunthe, Makharany; sari, Dwy Puspita; Anugrah, Ade Nur (Journal of Posthumanism, 2025)
The autonomous learning curriculum, a recent paradigm shift in Indonesia, guarantees student-centered learning techniques. The goal of implementing the curriculum for autonomous learning is to address t e educational problems of the period of Industrial Revolution 4.0. Using problem-based learning (PBL) learning modules to enhance scientific literacy and high-level thinking skills (HOT) is one of them. The validity of problem-based learning modules on buffer solution content, student responses to the module, the increase in scientific literacy comprehension, the development of high level thinking abilities in students taught with PBL-based modules, and the module's efficacy are all the objectives of this study. The study was carried out in North Sumatra, Indonesia, at SMA Negeri 1 Ronggurnihuta. Purposively, samples were drawn from a single class of twenty-eight pupils. This study used a 4D development approach (Define, Design, Develop, Disseminate) in conjunction with research and development (R&D) development research. Questionnaires and validation sheets served as the study's research tools. According to the study's first phase, the problem-based learning module's average validation scores on the Buffer Solution content fell into the extremely high category of 84.75%. However, the average student response to the program fell into the very good category with 87%. Essay-style questions with distinct indications are used in the Science Literacy and High-Order Thinking Skills assessments. According to the normalized Gain test results, students' high-level thinking abilities increased by 82.16 in the high category and their science literacy increased by 65.83% in the moderate category. This study suggests that the problem-based learning module on the buffer solution material is successful in enhancing students' science literacy and critical thinking abilities based on the gain conversion findings.